Il ruolo della pedagogia nella guerra attuale - Daniela Sarsini (Firenze University Press, 2022)
The paper reflects on the contribution that pedagogy can, and must, make to politics to reaffirm the values of peace and democracy: this is a particularly urgent task at the present time and for future scenarios.